Understanding the roles and impact of Solute Carrier Transporters OCT1, OCTN1, and OCTN2 in lung epithelia - Magana Gomez, Paulyna Gabriela (2024)
The organic cation transporters (OCT) 1, 2, and 3, along with the novel organic cation transporters (OCTN) 1 and 2, are members of the Solute Carrier 22 (SLC22) family, these transporters play significant roles in mediating the intracellular movement of endogenous compounds, including neurotransmitters, L-carnitine, and ergothioneine. Furthermore, numerous drugs used in the management of respiratory disorders exhibit cationic properties at physiological pH, making them potential substrates of OCT/Ns. Additionally, the involvement of OCT/Ns in lung diseases, suggests their possible relevance as novel drug targets Moreover, these proteins significantly influence the efficacy of specific anti-cancer drugs, as the transport of these compounds is mediated by OCT/Ns.